Test information and it using - Beatričė Andziulienė; Arūnas Andziulis; Sonata Bakanauskaitė (Lietuvos Matematikos Rinkinys)
The questions of quality of test and test information by using Items Response Theory (IRT) are discussed in this work. Using the IRT gives many chances to make an effective test: